Customer knowledge management in the insurance industry in Malaysia. The role of knowledge sharing, market and technology turbulence / Ahmad Suffian Mohd Zahari - Mohd Zahari, Ahmad Suffian (2014)
Customer Knowledge Management (CKM) is derived from the knowledge management concept, which can be applied by organizations strategies to satisfy their customers’ needs and wants. The dimensions of customer knowledge management are developed from the knowledge flow perspectives such as knowledge for customers, knowledge about customers and knowledge from customers. In this manner, CKM refers to the management of knowledge for customers, knowledge about customers and knowledge from customers to improve organizational performance. This study examined the effects of CKM dimensions in influencing organizational performance in insurance industry in Malaysia. This study also investigated the influence of moderating effects of market and technology turbulence in the relationship between knowledge sharing and organizational performance and between CKM and organizational performance. This study also examined the mediating effects of knowledge sharing in the relationship between CKM and organizational performance. A total of 180 managers from various insurance companies in Malaysia are involved in this study by voluntarily completing the survey questionnaires. A series of statistical analyses were applied including descriptive analysis, factor analysis, reliability analysis, correlation analysis and multiple regressions analysis using the SPSS software. The finding of this study contributed to advance understanding of CKM and organizational performance in a number of important ways. First, the results of the study indicate support for the relationship between CKM dimensions and organizational performance. Knowledge for customers, knowledge about customers and knowledge from customers were found to have significant influences on organizational performance. Second, the results reveal that CKM dimensions have significant influence on knowledge sharing. With regard to the relationship between knowledge sharing and organizational performance, the results show that knowledge sharing was found to be significantly associated with organizational performance. Furthermore, the results also indicate that knowledge sharing as a mediator significantly mediated the relationship between CKM and organizational performance. Looking at the moderating effect of technology turbulence, the results show that technology turbulence significantly moderated the relationship between knowledge sharing and organizational performance. In contrast, market turbulence did not moderate the relationship between knowledge sharing and organizational performance. Finally, regarding the moderating effect of market turbulence on the relationship between CKM dimensions and organizational performance, the study revealed that market turbulence did not moderate the relationship between CKM and organizational performance. Furthermore, technology turbulence also did not moderate the relationship between CKM dimensions and organizational performance. The findings of this study contribute to knowledge management and marketing literature by adding new empirical evidence on the relationship between CKM, organizational performance, knowledge sharing, market and technology turbulence. In terms of managerial implications, the findings help insurance companies in organizing CKM dimensions, particularly in strategizing, marketing, decision making and positioning themselves in the insurance industry.